การศึกษาเครื่องยนต์ที่มีอากาศอัดเป็นต้นกำลัง - ภูพิงค์ แต้ปีติกุล (จุฬาลงกรณ์มหาวิทยาลัย, 2009)
The energy transform to the mechanical power is established from engine. Recently, the most popular and high efficiency engine is internal combustion engine that transforms chemical energy as petroleum fuel. Now, the worlds know that the internal combustion engine is the main cause of pollution problem and many problems in our environment. From limited energy of petroleum fuel that inspirited to innovate any new prime movers, the energy directly transforms from solar differential energy. One ideal of the other is the energy transform from compressed air engine that uses to storage energy and applies to use in small vehicle. The prototype engine that consists of high pressure state expander and low pressure state expander for increasing thermodynamic efficiency and more mechanical power from single state expansion. Firstly, high pressure air flows to the pressure regulator for pressure throttling that reduces pressure approximately 35- 20 bar, before flows to the system. The system composes two sliding vane expanders; another has five sliding vanes. Volume of high pressure state expander is 12.5 cc and volume of low pressure state expander is 60 cc .the study process is separated into two sections, design and assembly prototype is the first section and experimental section is basic characteristic education. From experimental data ,the highest total power is 752 watts when the inlet pressure is 30 bar and ambient temperature of nitrogen to the engine. The total power is the sum of high pressure state expnsion giving 252 watts at 1925 rpm, 1.25 N.m in torque and low pressure state expansion giving 500 watts at 1475 rpm,3.24 N.m in torque. In conclusion, the mechanical efficiency of prototype engine is very low compares to the theoretical isothermal efficiency.